Effect of Process Variables on the Mechanical Characteristics of form Fabricated Materials - Chaudhari V.P; Patil A.D; Kalpande S.D (International Journal of Machine Systems and Manufacturing Technology, 2025)
Additive manufacturing prominent rapidly advancing technologies for producing 3D-printed products. Initially developed by stratasys, FDM technology emerged during the 1980s. This additive manufacturing technique builds products by extruding semi-molten material through a nozzle onto a platform. PLA and ABS are among numerous thermoplastics that are commonly used as filaments in this procedure. Purpose of research was to observe the effect of variables such as infill percentage, bed temperature, printing speed on the output variables of ABS printed part. The variables namely tensile strength and surface topography are considered for the study. The study uses the Taguchi L27 orthogonal array and the analysis of variance (ANOVA) statistical method to evaluate the importance of the input parameters. The most important manufactured factor affecting stiffness is the infill density. Higher infill density leads to more strength due to larger material volume which causes strong internal support. Effect of printing speed and bed temperature also studied. Printing speed adversely affect on surface texture of printed part. Excessive bed temperature leads to reduction of adhesion and causing first layer to detach or warp. These findings highlight the need of optimization of 3D printing parameters, ensuring quality while reducing residual stress and warping.
Keywords: FDM; Infill density; PLA; bed temperature; printing speed